Evaluation of the Ti6Al4V Alloy Plasma Nitride for Orthopedic Implants: in Vitro Biocompatibility Study in Simulated Body Fluid - abdulhamied, Zainab.T; Khalaf, Hanaa.K; Hassan, Aqeel.F; Ashour, Shahlaa.J (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
In view of this work, plasma nitriding was executed on Ti-6Al-4V and the effect of nitriding by using glow discharge with 2 mbar of Ar+N2 gas on corrosion resistance with different nitriding time and studied. The structure properties and the external appearance for alloys were performed with x-ray diffraction and optical microscopic. The investigation of XRD indicates the Ti alloys are polycrystalline with a cubic type (bcc). When the external appearance of the surface indicates was of β+α structure which have been better technical properties on biomedical application. The biocompatibility investigation of nitride alloys in vitro medium containing human body fluid: we showed a layer of hydroxyapatite HAP which might be considered in good biocompatible ceramic with the expected ability for chemical bonding with bone.